2019
DOI: 10.1093/aob/mcz040
|View full text |Cite
|
Sign up to set email alerts
|

Hypernodulating soybean mutant line nod4 lacking ‘Autoregulation of Nodulation’ (AON) has limited root-to-shoot water transport capacity

Abstract: Background and Aims Although hypernodulating phenotype mutants of legumes, such as soybean, possess a high leaf N content, the large number of root nodules decreases carbohydrate availability for plant growth and seed yield. In addition, under conditions of high air vapour pressure deficit (VPD), hypernodulating plants show a limited capacity to replace water losses through transpiration, resulting in stomatal closure, and therefore decreased net photosynthetic rates. Here, we used hypernodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…This establishes a hydraulic pathway known as the soil-plant-atmosphere continuum. In this context, high root hydraulic conductivity plays a pivotal role in supplying water to the aerial parts of plants (Figueiredo et al 2014;Lopes et al 2019). Thus, investigating how plants respond to regulated de cit irrigation can help optimize water productivity (Fernández et al, 2020) and shed light on their tolerance and sensitivity to water de cit at different phenological stages (Coelho et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This establishes a hydraulic pathway known as the soil-plant-atmosphere continuum. In this context, high root hydraulic conductivity plays a pivotal role in supplying water to the aerial parts of plants (Figueiredo et al 2014;Lopes et al 2019). Thus, investigating how plants respond to regulated de cit irrigation can help optimize water productivity (Fernández et al, 2020) and shed light on their tolerance and sensitivity to water de cit at different phenological stages (Coelho et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A soybean AON-deficient mutant showed compromised root hydraulic conductivity and leaf water potential, indicating that AON contributes to water uptake and maintains leaf water status ( Caroline Silva Lopes et al 2019 ). Numerous investigations have been conducted on deducing the mechanism of AON; however, a few questions remain unanswered.…”
mentioning
confidence: 99%
“…Nonstructural carbohydrates are essential for meeting immediate carbon requirements in environmental conditions such as water-deficit stress. Caroline Silva Lopes et al (2019) showed that soybean AON-deficient mutants have poor ability to transport water from root to shoot, leading to less shoot water content and uncontrolled nodule number ( Caroline Silva Lopes et al 2019 ). These findings led to the hypothesis that the shoot of AON-deficient mutants is deprived of water.…”
mentioning
confidence: 99%